Designing a Photobook of Historical Buildings in the City of Surabaya - Hilaluzzaman, Muhammad; Koesoemadinata, Dr. Moh. Isa Pramana (VCD, 2019)
Surabaya is the birthplace of the real Indonesian Revolution of Independence with the occurrence of November 10th event, where a major battle between Indonesia and the Allied Force took place remembered as the City of Heroes. Many historical buildings as witnesses are still standing firmly until today, but as the large population increases, the depletion of vacant land in Surabaya has caused some locations to evict old unused buildings including historical buildings. Concerns arise when there are several historical sites began to be destroyed although there are regulations issued by government to protect them. A preservation effort is taken by designing a photobook as documentation and also will served as historical reference for the public. The goal is to provide information about the historical places of Surabaya by comparing the previous conditions to its current condition. The data were collected using observation method, literature studies, interview and distributing questionnaires to the targeted respondents who were all interested in studying history and travel. The results of this research is a photobook of historical buildings in the city of Surabaya which will be a reference of Indonesian independence history and also perpetuate the buildings and historical places that still exist today.